The Effect of Chromium Exposure on Creatinine and Bun Level of Tanners in Leather Industry in Magetan - Siti Asiah1 , Abdul Rohim Tualeka1 , Y. Denny Ardyanto W1 (Indian Journal of Forensic Medicine & Toxicology, 2020)
Chromium in the leather tanning industry can have an impact on workers’ health. Kidney disease is often referred to as a side effect from exposure to chromium. Measurement of creatinine and BUN level is a method of examining kidney function. The purpose of this study was to analyze the effect of chromium exposure on creatinine and BUN level in leather tanning workers in small leather industry in Magetan. This type of research is observational with cross sectional design. The sample of the study was 13 exposed worker groups namely chromium operators and 13 unexposed groups namely administrative workers. The results showed that there were differences in the average levels of urine chromium in chromium operators and administrative workers (p-value = 0,000), there were differences in the average creatinine levels in chromium operators and administrative workers (p-value = 0,031), and there were no difference in the average level of BUN in chromium operators and administrative workers (p-value = 0,644). There were no influence of chromium levels in urine on the increase in creatinine levels (p-value = 0,189) and BUN (p-value = 0,854) in tanning workers, with a significance value of p-value> 0,05. The conclusion of this study had that chromium was no effect on creatinine and BUN levels. High levels of urine chromium in tanning workers indicate a health risk that requires control effort. Suggestion given is that the tanners need periodic health examination, keep personal hygiene before and after working as well as using Personal Protective Equipment (PPE).